Metal ions binding and colloidal destabilization in the model systems: Implication on the magnesium chloride coagulation mechanism in tofu making - Qianru Li; Yufei Hua; Xingfei Li; Xiangzhen Kong; Caimeng Zhang; Yeming Chen (Food Chemistry: X)
MgCl2-induced soymilk coagulation mechanism in tofu making was explored from perspectives of Mg2+ binding and colloidal properties in model systems. Isothermal titration calorimetry of bovine serum albumin (BSA)-small molecule mixtures revealed proteins contributed negligibly to Mg2+ binding sites, instead, substantial Mg2+ were bound by soymilk-borne small molecules. The results thus suggested the “protein-Mg2+-protein bridge” was hardly formed in tofu making. Zeta potentials for both BSA-small molecule system and defatted soymilk changed in a similar pattern relative to the unbound Mg2+ concentration, indicating only those small molecules-unbound Mg2+ effectively neutralized the electronegative charges on protein colloidal particles. Turbidity and particle size results revealed a critical zeta potential (−11 mV) was required to induce marked Mg2+-defatted soymilk coagulation. For heated defatted soymilks, a critical minimum protein concentration (8 mg/mL) was needed to observe the significant Mg2+-induced coagulation. This study is expected to deepen our understanding of Mg2+ coagulation mechanism in tofu making.